PERANCANGAN SISTEM INFORMASI SERVICE SEPEDA MOTOR PADA PRIMA SERVICE TEMBILAHAN - Samsudin Samsudin (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2014)
Prima Service to represent one of company active in service of motorcycles service, where system exist in is Prima Service still not yet gratified incoming consumer to service and still there are problemss that is as follows : consumer await beforehand cashier record-keeping of related to consumer data, goods and vehicle so that need time 4-5 minute can become 3-2 minute, enumeration of expense of service / transaction still use calculator with existence of this system have been made automatically, the happening of difficulty storey level look for data purchasing of access goods which have been because data purchasing of access goods still in form of archives now there in database and also making of report eat old time now have computerized better. In development of information system of service, writer use method of waterfall Ianguage and of courses which is used in designing and information system implementation of service visual basic 6.0 and database the used MYSQL Keyword : Information Systems, Service Motocycles, Flowchart Document, Diagram Context, Data of Flow Diagram